Bacterial communities in a subarctic stream network: Spatial and seasonal patterns of benthic biofilm and bacterioplankton. Issue 24 (17th October 2022) - Malazarte, Jacqueline; Muotka, Timo; Jyväsjärvi, Jussi; Lehosmaa, Kaisa; Nyberg, Joel; Huttunen, Kaisa‐Leena
Abstract: Water‐column bacterial communities are assembled by different mechanisms at different stream network positions, with headwater communities being controlled by mass effects (advection of bacteria from terrestrial soils) while downstream communities are mainly driven by environmental sorting. Conversely, benthic biofilms are colonized largely by the same set of taxa across the entire network. However, direct comparisons of biofilm and bacterioplankton communities along whole stream networks are rare. We used 16S rRNA gene amplicon sequencing to explore the spatiotemporal variability of benthic biofilm (2 weeks old vs. mature biofilm) and water‐column communities at different network positions of a subarctic stream from early summer to late autumn. Amplicon sequence variant (ASV) richness of mature biofilm was about 2.5 times higher than that of early biofilm, yet the pattern of seasonality was the same, with the highest richness in midsummer. Biofilm bacterial richness was unrelated to network position whereas bacterioplankton diversity was negatively related to water residence time and distance from the source. This pattern of decreasing diversity along the network was strongest around midsummer and diminished greatly as water level increased towards autumn. Biofilm communities were phylogenetically clustered at all network positions while bacterioplankton assemblages were phylogenetically clustered only at the most downstream site. Both early and mature biofilm communities already differed significantly between upstream (1st order) and midstream (2nd order) sections. Network position was also related to variation in bacterioplankton communities, with upstream sites harbouring substantially more unique taxa (44% of all upstream taxa) than midstream (20%) or downstream (8%) sites. Some of the taxa that were dominant in downstream sections were already present in the upmost headwaters, and even in riparian soils, where they were very rare (relative abundance <0.01%). These patterns in species diversity and taxonomic and phylogenetic community composition of the riverine bacterial metacommunity were particularly strong for water‐column communities, whereas both early and mature biofilm exhibited weaker spatial patterns. Our study demonstrated the benefits of studying bacterioplankton and biofilm communities simultaneously to allow testing of ecological hypotheses about biodiversity patterns in freshwater bacteria.